Bacteriophage lytic enzymes and their engineering towards improved antibacterial efficacy - Proença, Daniela Sofia Moreira, 1983- (2014)
Tese de doutoramento, Farmácia (Microbiologia), Universidade de Lisboa, Faculdade de Farmácia, 2015